Peran Event Pariwisata Rang Solok Baralek Gadang 2023 dalam Pengembangan Pariwisata Kota Solok - Denisa, Elena Jovanka; Setianti, Yanti; Nugraha, Aat Ruchiat (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Tourism events are events that are held intentionally and planned for the purpose of tourism development. Tourism events have four roles, namely as an attraction, image shaper, catalyst and animator. The Solok City Tourism Office is holding a food security-based tourism event called Rang Solok Baralek Gadang 2023. This research aims to determine the role of the Rang Solok Baralek Gadang 2023 tourism event in the development of tourism in Solok City as a Rice City. This research is qualitative research with a postpositivism paradigm and case study method. Data was collected through interviews, observation and documentation studies. The technique for determining key informants is purposive sampling, while data validation is carried out by source triangulation. The research results show that the role of Rang Solok Baralek Gadang 2023 in the development of Solok City tourism is as an attraction, image maker and catalyst.